Effects of family and neighborhood vulnerability on dual language learner and monolingual children’s preschool outcomes - Frechette, Liz; Castle, Sherri; Jeon, Shinyoung; Horm, Diane; Martinez, Irving; Vega Ruvalcaba, Denise; Schaefer, Shawn (Frontiers in Education, 2023)
Introduction Research has documented that home and neighborhood contexts of children from low-income families are associated with lower cognitive and social–emotional skills than their higher-income peers. Even though over a third of young children growing up in poverty are dual language learners (DLLs), little research has examined how contextual effects differ between DLL and monolingual children. The current study examines how these two contexts, neighborhood vulnerability and family socioeconomic risk, impact executive function (EF) and social–emotional skills in DLL and monolingual preschoolers. Methods A secondary analysis was completed on data from two Head Start programs. A series of cross-classified models with interactions were conducted to examine the moderating role of DLL status on associations between neighborhood vulnerability and family risk and preschoolers’ EF and social-emotional skills. Results Proficient bilingual children’s EF skills were not impacted by neighborhood risks, suggesting that proficient bilingual children may have more opportunities to grow their EF skills when switching between English and Spanish regardless of neighborhood context. An unexpected result occurred for emergent bilingual children who were reported to demonstrate fewer behavior problems regardless of family risk, highlighting the importance of ensuring all DLL families have access to resources to promote their children’s social–emotional skills; and teachers have the proper training to support the behaviors of children in their classroom with varying levels of English proficiency. Discussion Although speaking two languages may be a protective factor for young DLLs growing up in poverty, little research has examined how contextual effects differ between DLL and monolingual children. The current study contributes by examining how DLL status, especially two different DLL statuses (i.e., Proficient Bilinguals and Emergent Bilinguals), may vary as a buffer in moderating the negative associations between collective neighborhood vulnerability, individual family risk, and children’s EF and social–emotional skills.